Sectorial Border Effects in the European Single Market: an Explanation through Industrial Concentration - Gianluca Cafiso (European Central Bank (ECB), 2009)
The purpose of this paper is to explain the relation between the Border Effect and industrial concentration. This is achieved by founding this relation on the Home Market Effect and testing the robustness of this foundation through an application to the European Single Market. A sectorial Gravity Equation is estimated using different econometric estimators, in particular we discuss a recently suggested technique for the estimation of log-linear CES models. Overall, our findings suggest a steady relation between the Border Effect and industrial concentration. Besides, the analysis of industrial concentration through a synthetic index provides us with valuable insights into the structure of the European industry.
Keywords: F10; F12; F15; 330; Border Effect; European Single Market; Home Market Effect; Industrial Concentration; Trade; Internationale Wirtschaftsbeziehungen; Außenwirtschaftstheorie; Handelseffekt; Unternehmenskonzentration; EU-Binnenmarkt; Gravitationsmodell; EU-Staaten